2018
DOI: 10.1111/mmi.13972
|View full text |Cite
|
Sign up to set email alerts
|

Homologs from sulfur oxidation (Sox) and methanol dehydrogenation (Xox) enzyme systems collaborate to give rise to a novel pathway of chemolithotrophic tetrathionate oxidation

Abstract: The SoxXAYZB(CD) -mediated pathway of bacterial sulfur-chemolithotrophy explains the oxidation of thiosulfate, sulfide, sulfur and sulfite but not tetrathionate. Advenella kashmirensis, which oxidizes tetrathionate to sulfate, besides forming it as an intermediate during thiosulfate oxidation, possesses a soxCDYZAXOB operon. Knock-out mutations proved that only SoxBCD is involved in A. kashmirensis tetrathionate oxidation, whereas thiosulfate-to-tetrathionate conversion is Sox independent. Expression of two gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 69 publications
4
52
0
Order By: Relevance
“…Whereas the SST genome annotation did not reveal any tetrathionate hydrolase (tetH) gene, three consecutive ORFs (locus tags DIE28_01705, DIE28_01710 and DIE28_01720), homologous to the xoxF, xoxG and xoxJ genes of the prototypical methanol-oxidizer Methylobacterium extorquens AM1 (Nakagawa et al, 2012;Keltjens et al, 2014;Pol et al, 2014;Skovran and 395 Martinez-Gomez, 2015;Chu and Lidstrom, 2016) were detected. Albeit the xoxF gene of SST was found to have ~75% and 69% translated amino acid sequence identities with the typical PQQbinding XoxF homologs of AM1 and the ThdT variant of XoxF reported from A. kashmirensis (Pyne et al, 2018) respectively, the annotated genome sequence of SST deposited in the GenBank designates the locus DIE28_01705 as a pseudogene, apparently due to a frame shift caused by a 400 missing guanine nucleotide in between positions 1161 and 1162 of the ORF. However, a manual scrutiny of the reads aligned to this region of the SST genome showed that 153 and 173 reads taking part in the assembly contained and lacked the guanine in the above mentioned position respectively, while 36 others had an ambiguous base call in this nucleotide position (notably, proportion of ambiguous base calls across this xoxF ORF was also quite high).…”
Section: Whole Genome Sequnceingof P Thiocyanatus Sst and Identificamentioning
confidence: 97%
See 4 more Smart Citations
“…Whereas the SST genome annotation did not reveal any tetrathionate hydrolase (tetH) gene, three consecutive ORFs (locus tags DIE28_01705, DIE28_01710 and DIE28_01720), homologous to the xoxF, xoxG and xoxJ genes of the prototypical methanol-oxidizer Methylobacterium extorquens AM1 (Nakagawa et al, 2012;Keltjens et al, 2014;Pol et al, 2014;Skovran and 395 Martinez-Gomez, 2015;Chu and Lidstrom, 2016) were detected. Albeit the xoxF gene of SST was found to have ~75% and 69% translated amino acid sequence identities with the typical PQQbinding XoxF homologs of AM1 and the ThdT variant of XoxF reported from A. kashmirensis (Pyne et al, 2018) respectively, the annotated genome sequence of SST deposited in the GenBank designates the locus DIE28_01705 as a pseudogene, apparently due to a frame shift caused by a 400 missing guanine nucleotide in between positions 1161 and 1162 of the ORF. However, a manual scrutiny of the reads aligned to this region of the SST genome showed that 153 and 173 reads taking part in the assembly contained and lacked the guanine in the above mentioned position respectively, while 36 others had an ambiguous base call in this nucleotide position (notably, proportion of ambiguous base calls across this xoxF ORF was also quite high).…”
Section: Whole Genome Sequnceingof P Thiocyanatus Sst and Identificamentioning
confidence: 97%
“…However, a manual scrutiny of the reads aligned to this region of the SST genome showed that 153 and 173 reads taking part in the assembly contained and lacked the guanine in the above mentioned position respectively, while 36 others had an ambiguous base call in this nucleotide position (notably, proportion of ambiguous base calls across this xoxF ORF was also quite high). As capillary 405 sequencing also failed to resolve this issue unambiguously, we decided to knock this gene out and confirm whether tetrathionate oxidation in SST proceeded via a ThdT-mediated glutathionecoupled mechanism similar to the one described for A. kashmirensis (Pyne et al, 2017(Pyne et al, , 2018.…”
Section: Whole Genome Sequnceingof P Thiocyanatus Sst and Identificamentioning
confidence: 99%
See 3 more Smart Citations